Developing a CBT-Based Intervention Program for Reducing School Burnout and Investigating Its Effectiveness With Mixed Methods Research - Ulaş, Sümeyye; Seçer, İsmaİl (Frontiers in Psychology, 2022)
This study sets out to develop a cognitive-behavioral therapy-based psychoeducation application to reduce the school burnout levels of secondary school students and to test its effectiveness with the mixed methods research design. For this purpose, qualitative data have been included in the process at three different steps, before, during and after the experimental application involving an intervention application. The application of the intervention of the research has been carried out with an experimental design with pretest-posttest control group, which is one of the true experimental designs. Experimental and control groups have been determined with 30 students reached by nested sampling method, and the CBT-based psychoeducation practice developed during the research process has been carried out for 9 weeks in the experimental group. During the research, descriptive analysis and content analysis methods have been used in the analysis of qualitative data, normality analysis and One-Way Analysis of Covariance have been used in the analysis of quantitative data. Findings obtained from the study show that CBT-based psychoeducation practice is an effective approach in reducing school burnout. It has also been determined that the findings obtained from the analysis of the documents obtained during the application and findings from the interview process done after the application coincided with the findings of quantitative methods, and the qualitative findings adequately explain the quantitative findings.